2002
DOI: 10.1089/108076802317373914
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Immortalized Human Corneal Epithelial Cell Line and Rabbit Corneal Epithelial Cell Culture in Cytotoxicity Testing

Abstract: The cytotoxicity of benzalkonium chloride (BAC) and disodium edetate (EDTA) was evaluated in vitro in rabbit corneal epithelial primary cells and in the immortalized human corneal epithelial cell line SV40. Cell injury was assessed by lactate dehydrogenase (LDH) leakage and by reduction of the tetrazolium salt WST-1 to formazan by mitochondrial metabolic activity. Cell cultures were exposed to test compounds both in serum-free and in serum-containing medium. Although WST-1 and LDH tests measured different phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Both cell lines exhibit phenotypic and functional properties similar to those of their primary cultured counterparts while permitting continuous growth for >100 passages (Araki et al, 1993;Huhtala et al, 2002). Passages <16 were used in the present study.…”
Section: Cell Culturementioning
confidence: 99%
“…Both cell lines exhibit phenotypic and functional properties similar to those of their primary cultured counterparts while permitting continuous growth for >100 passages (Araki et al, 1993;Huhtala et al, 2002). Passages <16 were used in the present study.…”
Section: Cell Culturementioning
confidence: 99%
“…Furthermore, Huhtala et al (2002) have reported that it was possible to obtain more reliable data with less variation using WST-1 rather than LDH release. Mitochondrial respiration may be a useful parameter to evaluate cytotoxicity in the case of in vitro hepato-toxicity screening, since mitochondrial respiration can be detected during the early stage of exposure and well reflects the toxicological changes occurring inside the cells.…”
Section: Detection Of Cytotoxicitymentioning
confidence: 99%
“…In addition, albumin secretion, urea synthesis, alanine aminotransferase, aspartate aminotransferase, intracellular glutathione levels, etc., are generally used as endpoints for in vitro hepatocellular function (Riss and Moravec, 2004;Wang et al, 2002;Hamid et al, 2004;Viluksela et al, 1996;Huhtala et al, 2002;Smet et al, 2000;Kang et al, 2004;Walker et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This cell line exhibits phenotypic and functional properties similar to those of its primary culture counterpart, while permitting continuous growth. 12,[25][26][27] Passages 17-25 were used in this study. Cells were grown to 80-90% confluence, serum-starved, and deprived of growth factors for 24 h before experimentation unless otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%